Strengthening The NU Cultural Values Through The Tradition Of Napak Tilas (Pilgrimage To Maqbaroh KH. Muntaha) Females Student Roudlotul Huffadz PPTQ Al-Asy'ariyah Central Kalibeber Wonosobo - ‘Azmi, Nabiilah Tsabitul; Ma’rifah, Isnaeni; Mubin, Nurul (DAS Institute, 2024)
This study was conducted in order to describe the strengthening of NU cultural values through the tradition of napak tilas (retracement) pilgrimage to the tomb of Al Maghfurlah KH. Muntaha Al Hafidz especially for female students of Roudlotul Huffadz, Pondok Pesantren Tahfidzul Qur'an Al-Asy'ariyah Pusat Kalibeber Wonosobo. Pilgrimage to the grave is one of the NU traditions that is still carried out today. Looking at the rapid development of the era with various forms of influence on the young generation who are growing up in instability, pilgrimage to the grave becomes a practice that can be used as a habit for students to become a fortress from the negative impacts of the surrounding environment. The tradition of Napak Tilas functions as a medium to strengthen the cultural values of Nahdlatul Ulama (NU) among female students. The pilgrimage to the tomb of KH. Muntaha is not only intended to commemorate the ulama figure, but also as a means of spiritual and cultural education that instills awareness of the importance of appreciating Islamic teachings and NU traditions. This study uses a qualitative approach to analyze the impact of these activities on the identity of students and the preservation of NU values in the pesantren environment. Interviews and observations are the methods of data collection for this study. The results show that this tradition strengthens a sense of togetherness, fosters a spirit of learning, and increases students' love for their cultural heritage